Acoustic performance mixture of natural fibres of oil palm frond (Opf) and empty fruit bunch (efb) - Mageswaran R.C.; Ewe L.S.; Yew W.K.; Mohammad Nazhan N.; Zawawi I. (Trans Tech Publications Ltd, 2023)
Acoustic impedance; Acoustic wave absorption; Fruits; Natural fibers; Palm oil; Sound insulating materials; Acoustic performance; Acoustics property; Empty fruit bunch; Empty fruit bunches; Oil palm; Oil palm frond; Scanning electron microscope; Sound absorption coefficient; Sound absorption coefficients; Scanning electron microscopy